The Effect of Guided Inquiry Learning with Multi Representation of the Science Process Skills and Concepts Mastery of Natural Science of Junior High School Students - Muhammad Rizal (Jurnal Pendidikan Sains, 2014)
Pengaruh Pembelajaran Inkuiri Terbimbing dengan Multi Representasi terhadap Keterampilan Proses Sains dan Penguasaan Konsep IPA Siswa SMP Abstract: The aims of this study to determine the effect of guided inquiry learning with multi representations on the mastery of science process skills and sciences concept mastery in junior high school students. This quasi experimental study use post-test only control group design involved 8th grade students that selected by simple random sampling. Experimental class used guided inquiry learning with multi representation and control class used guided inquiry learning. The results showed that there are no differences science process skills between experimental class students and control class students, while the mastery of science concept experimental class students differences than students control class students, and science process skills students have positive correlation with science concept mastery.Key Words: guided inquiry, multi representation, science process skills, science concept mastery Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran inkuiri terbimbing dengan multi representasi terhadap keterampilan proses sains dan penguasaan konsep IPA siswa SMP. Penelitian kuasi eksperimen ini menggunakan post-test only control group design dengan melibatkan siswa kelas VIII yang dipilih secara simple random sampling. Kelas eksperimen menggunakan pembelajaran inkuri terbimbing dengan multi representasi dan kelas kontrol menggunakan pembelajaran inkuiri terbimbing. Hasil penelitian menunjukkan keterampilan proses sains siswa kelas eksperimen tidak berbeda dengan siswa kelas kontrol, sementara penguasaan konsep IPA siswa kelas eksperimen berbeda dari siswa kelas kontrol, dan keterampilan proses sains siswa berkorelasi positif dengan penguasaan konsep IPA.Kata kunci: inkuiri terbimbing, multi representasi, keterampilan proses sains, penguasaan konsep IPA